2013
DOI: 10.1097/iae.0b013e3182923477
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Healthy Children

Abstract: The data, obtained using enhanced depth imaging optical coherence tomography, provide the choroidal thickness profile of healthy children. The characteristic choroidal thickness profile in children suggests a redistribution process of choroidal tissue with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
91
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 19 publications
13
91
7
1
Order By: Relevance
“…11 Among these studies, only Park et al reported a negative correlation between SFCT and age. 9 However, Read et al 10 and Bidaut-Garnier et al 11 have reported that choroidal thickness increases significantly from early childhood to adolescence and is inversely correlated to AL in children. It is also important to emphasize that in Park et al 9 study, patients with SE þ / À 6 diopter were recruited, which was much higher SE refractive error compared with the inclusion criteria of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Among these studies, only Park et al reported a negative correlation between SFCT and age. 9 However, Read et al 10 and Bidaut-Garnier et al 11 have reported that choroidal thickness increases significantly from early childhood to adolescence and is inversely correlated to AL in children. It is also important to emphasize that in Park et al 9 study, patients with SE þ / À 6 diopter were recruited, which was much higher SE refractive error compared with the inclusion criteria of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19] Also, there is recent data on the hemodynamic effect of chemicals-sildenafil and nicotine-on choroid, obtained by OCT. 20,21 In our population of 160 patients aged 4-23 years, we found a mean SFCT of 308 mm with substantial variation between individuals, which was consistent with previous studies in adults. 4,22 Recent studies examining in vivo choroidal thickness with OCT in children have reported mean SFCT values of 348 mm (in 48 Korean children aged 4-10 years), 9 330 mm (in 194 children aged 4-12 years), 10 and 342 mm (in 174 children aged 3.5-15 years). 11 Among these studies, only Park et al reported a negative correlation between SFCT and age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is crucial to study repeatability and reproducibility because of the manual segmentation and the other mentioned parameters. Comparison with previous studies is difficult because of the different line scans performed with various instruments, variability in the ages and sexes of the populations being evaluated or the different statistical methodologies used.A number of studies have characterized healthy choroidal thickness, one of the most studied parameters, as having mean subfoveal choroidal thickness values lower than 300µm 7,9,10,20,23,25 or higher that 300µm 6,8,13,24,[26][27][28] , with a range from 202.6±83.5µm 9 to 355±73µm 8 or 354±111µm …”
mentioning
confidence: 99%